2019
DOI: 10.1016/j.bioactmat.2018.08.003
|View full text |Cite|
|
Sign up to set email alerts
|

Initial formation of corrosion products on pure zinc in saline solution

Abstract: Corrosion product formed on zinc sample during 2 weeks immersion in saline solution has been investigated. The corrosion layer morphology as well as its chemical composition, was analyzed using scanning electron microscopy (SEM), x-ray diffraction (XRD), x-ray photoelectron spectroscopy (XPS) and Fourier transform infrared spectroscopy (FTIR). Electrochemical measurement was used to analyze the corrosion behavior. Zinc oxide, zinc hydroxide and zinc hydroxide chloride were formed on zinc surface in saline solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
77
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(94 citation statements)
references
References 43 publications
11
77
0
6
Order By: Relevance
“…2 that E ocp in both sterile and Bacillus systems has shifted positively during the first day. It indicated that a product film developed in the early stage of the experiment due to the material of 10MnNiCrCu steel itself, which changed the state of the electrode surface and protected it temporarily 17 . Since then, the E ocp in sterile system shifted negatively due to oxygen absorption corrosion and stabilized after 5 days 18 .…”
Section: Resultsmentioning
confidence: 99%
“…2 that E ocp in both sterile and Bacillus systems has shifted positively during the first day. It indicated that a product film developed in the early stage of the experiment due to the material of 10MnNiCrCu steel itself, which changed the state of the electrode surface and protected it temporarily 17 . Since then, the E ocp in sterile system shifted negatively due to oxygen absorption corrosion and stabilized after 5 days 18 .…”
Section: Resultsmentioning
confidence: 99%
“…Ions of Cl − and SO 4 2− are likely to cause pit corrosion, leading to the local acceleration of iron degradation [ 51 ]. What's more, Cl − is also notorious for zinc degradation [ 52 ], which may have influence on the degradation of iron. In addition, endothelial cell coverages on struts of permanent stents and bioresorbable scaffolds are normally lower than those between struts, which is strengthened in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The in vitro corrosion behavior of pure Zn in different corrosive mediums has been extensively investigated by researchers [ 85 , 256 , [267] , [268] , [269] ]. For example, the corrosion behavior of pure Zn in two corrosive solutions, PBS and RSS, and two natural body fluids, human plasma and whole blood, was first reported by Torne et al [ 256 ] and their results indicated that corrosion rates decreased with immersion time for plasma and whole blood, while they increased during immersion in PBS and RSS.…”
Section: Corrosion Mechanisms and Degradation Behaviors Of Pure Zn Anmentioning
confidence: 99%
“… Composition (wt.%) and manufacturing process Corrosion medium Immersion time (day) E corr (V) I corr (μA/cm 2 ) C.R (mm/y) Ref. C.R imm C.R ele Pure Zn Pure-Zn Saline 14 −1.25 16.73 0.063 [ 269 ] RSS 3 −1.049 0.10 0.094 [ 256 ] PBS 3 −0.994 0.03 0.021 WB 3 −1.130 0.11 0.104 HP 3 −1.094 0.19 0.179 SBF 14 −1.08 11.90 0.03 0.18 [ 264 ] Zn (foil) AP 28 −0.97 0.76 0.016 0.011 [ 267 ] Zn Cast ...…”
Section: Corrosion Mechanisms and Degradation Behaviors Of Pure Zn Anmentioning
confidence: 99%